Investigation of different polymeric membranes for removal of phenol from aqueous environment using pervaporation technique - Usama Eldemerdash; Alaa Dandash; Shaban Nosier; Heba Abdallah; Samah A. Hawash (Applied Water Science, 2024)
Abstract The removal of phenolic compounds from the water was of great importance due to their high toxicity. In this study, the separation of phenol from an aqueous environment by pervaporation technique using (PVA) polyvinyl alcohol, (CA) cellulose acetate, and (PVDF) polyvinylidene fluoride membranes was tested. The effect of feed concentration up to 9000 ppm, operating temperature from 25 to 65 °C, and flow rate ranging from 2 to 6 L h−1 on the separation performance was investigated. It was found that the CA membrane possessed a higher water flux of 348.25 kg m−2 h−1 and a separation factor of 49 compared to PVDF, and PVA/SA membranes at 65 °C and a flow rate of 6 L h−1. The properties and morphology of membranes were observed using mechanical properties, contact angle, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The results showed that CA has a lower contact angle of 48.3° indicating the hydrophilicity nature of the membrane, which enhances the separation process and explains the increases of water flux. Moreover, the mechanical properties test indicated that the mechanical strength of CA has a maximum tensile strength of 65.5 MPa and an % elongation of 48% compared to PVDF and PVA/SA which indicates lower roughness, manifesting its improved anti-fouling properties.